Mining Entity Attribute Synonyms via Compact Clustering - Li, Yanen; Hsu, Bo-June (Paul); Zhai, ChengXiang; Wang, Kuansan (CIKM, 2013)
Entity attribute values, such as "lord of the rings" for movie.title or "infant" for shoe.gender, are atomic components of entity expressions. Discovering alternative surface forms of attribute values is important for improving entity recognition and retrieval. In this work, we propose a novel compact clustering framework to jointly identify synonyms for a set of attribute values. The framework can integrate signals from multiple information sources into a similarity function between attribute values. And the weights of these signals are optimized in an unsupervised manner. Extensive experiments across multiple domains demonstrate the effectiveness of our clustering framework for mining entity attribute synonyms.